A Critical Review To Determine Whether A Correlation Can be Found between Magazine Reading and the Sexual Health of Adolescent Girls - Spencer, Louise (2008)
Adolescent sexual health is currently a main concern for the government with figures of Sexually Transmitted Infections (STIs) and Teenage Pregnancy at high levels. Poor sexual health can have significant health and social implications for adolescents. Despite government policy to improve sexual health, improvements are slow allowing young people to remain at risk. It is therefore of concern to health professionals, who are, at differing degrees, responsible for encouraging and facilitating positive sexual health practices, to investigate the influences on sexual health and determine how these can be used to promote positive practices. This study considers the role popular culture has to play in sexual health, with a particular focus on magazines aimed at adolescent girls.